Exploring Of Hibah Information Richness On Consumer Reception In Malaysia - Nursyuhadah Abdul Rahman; Nur Syairah Ani; Rafiatul Adlin Hj. Mohd Ruslan; Zulkarnian Hj. Ahmad; Arman Hj. Ahmad (International Journal of Business and Quality Research, 2023)
Hibah is the granting of ownership of a property from one party to another without any consideration (iwad) or rewards in return that happens during a hibah giver's lifetime, sincerely without any coercion or threats. This voluntary action is made without any purpose to glorify or honour anyone and it must come together with an agreement of offer and acceptance through ijab and qabul or any such words. In Islam, this action is considered as noble and dignified as it is not only to give an ownership transfer to the other party but also to protect the dispute among heirs after the death of the owner. However, besides the numerous advantages of hibah, the rate of its enforcement, subscription, and implementation in Malaysia remains low and many Muslims seem refused to accept because they do not understand or having a low understanding of this concept. Based on these motivations, this conceptual paper proposed variable to measure consumer understanding and acceptance towards hibah on asset to explore the actual factors that might contribute to high or low understanding towards hibah asset among Muslim consumers in Malaysia. It is hypothesized and predicted that all the variables are important to increase consumer understanding towards hibah asset in Malaysia. Instead of the proposed variable, this paper will also serve as a guideline for future researchers to extend the study empirically to testify the hypotheses. Moreover, the marketers especially the Islamic Estate Planners also could develop better marketing strategies to increase the consumers’ understanding, awareness and acceptance towards hibah asset in Malaysia.